Geographies of the COVID-19 pandemic. Issue 2 (July 2020) - Rose-Redwood, Reuben; Kitchin, Rob; Apostolopoulou, Elia; Rickards, Lauren; Blackman, Tyler; Crampton, Jeremy; Rossi, Ugo; Buckley, Michelle
The spread of the novel coronavirus (SARS-CoV-2) has resulted in the most devastating global public health crisis in over a century. At present, over 10 million people from around the world have contracted the Coronavirus Disease 2019 (COVID-19), leading to more than 500, 000 deaths globally. The global health crisis unleashed by the COVID-19 pandemic has been compounded by political, economic, and social crises that have exacerbated existing inequalities and disproportionately affected the most vulnerable segments of society. The global pandemic has had profoundly geographical consequences, and as the current crisis continues to unfold, there is a pressing need for geographers and other scholars to critically examine its fallout. This introductory article provides an overview of the current special issue on the geographies of the COVID-19 pandemic, which includes 42 commentaries written by contributors from across the globe. Collectively, the contributions in this special issue highlight the diverse theoretical perspectives, methodological approaches, and thematic foci that geographical scholarship can offer to better understand the uneven geographies of the Coronavirus/COVID-19.